Photocatalytic reduction and scavenging of Hg(ii) over templated-dewetted Au on TiO2 nanotubes. Issue 5 (11th December 2018) - Spanu, Davide; Bestetti, Alessandro; Hildebrand, Helga; Schmuki, Patrik; Altomare, Marco; Recchia, Sandro
Abstract : Au nanoparticles over TiO2 nanotubes strongly promote photocatalytic reduction/scavenging of Hg(ii ) through the formation of Hg2 Cl2 nanowires (or Au–Hg amalgams). Abstract : Gold-decorated TiO2 nanotubes were used for the photocatalytic abatement of Hg(ii ) in aqueous solutions. The presence of dewetted Au nanoparticles induces a strong enhancement of photocatalytic reduction and scavenging performances, with respect to naked TiO2 . In the presence of chlorides, a massive formation of Hg2 Cl2 nanowires, produced from Au nanoparticles, was observed using highly Au loaded photocatalysts to treat a 10 ppm Hg(ii ) solution. EDS and XPS confirmed the nature of the photo-produced nanowires. In the absence of chlorides and/or at lower Hg(ii ) starting concentrations, the scavenging of mercury proceeds through the formation of Hg–Au amalgams. Solar light driven Hg(ii ) abatements up to 90% were observed after 24 h. ICP-MS analysis revealed that the removed Hg(ii ) is accumulated on the photocatalyst surface. Regeneration of Hg-loaded exhaust photocatalysts was easily performed by anodic stripping of Hg(0) and Hg(i ) to Hg(ii ). After four catalytic-regeneration cycles, only a 10% decrease of activity was observed.